Syndromic epidermolysis bullosa simplex subtype due to mutations in the KLHL24 gene: series of case reports in Russian families - Kotalevskaya, Yulia Y.; Stepanov, Vadim A. (Frontiers in Medicine, 2024)
Objective Epidermolysis bullosa simplex (EBS) is a common, well-characterized type of epidermolysis bullosa. However, some rare syndromic EBS phenotypes are not well described. The accumulation of clinical descriptions of patients with syndromic subtypes of EBS is important for understanding the natural history of the disease and assessing genotype–phenotype correlations. Case summary We present a series of case reports of the syndromic subtype of EBS associated with mutations in the KLHL24 gene in seven patients from four unrelated families. The clinical features of this rare phenotype in children and adult patients are described in detail. In two families, we revealed pathogenic variant c.1A > G (p.Met1?) in the KLHL24 gene. The third family had c.3G > A (p.Met1?) mutation, and the fourth family had a novel de novo variant c.23del (p.Arg8AsnfsTer2). Conclusion The description of the clinical manifestations of the disease in two generations of EBS families with different genetic variants allows the assessment and prediction of the natural course and severity of the disease in these families, the risk of complications, and the planning of the amount of medical care necessary.